Hemodynamic fluid shear stress response genes and carotid intima-media thickness: a candidate gene association analysis in the cardiovascular health study. - Suchy-Dicey, Astrid M; Enquobahrie, Daniel A; Heckbert, Susan R; Rotter, Jerome I; Psaty, Bruce M; McKnight, Barbara (Int J Mol Epidemiol Genet, 2012)
OBJECTIVE: This study examined whether carotid artery intimal-medial thickness (cIMT) is associated with genetic variations (SNPs) in a hemodynamics-responsive gene pathway. METHODS: Subjects were Cardiovascular Health Study participants free of cardiovascular events at baseline (N=3388). Genotype was measured using Illumina 370CNV HumanHap chip. Carotid IMT was measured using ultrasound. Estimated mean differences in cIMT per additional minor allele for 366 SNPs in MAP2K5, MAPK7, MEF2A/C, and KLF2 were adjusted for sex, age, clinic, and medication use. SNP-SNP interactions were examined using logic regression for 71 tagSNPs. RESULTS: None of the associations was significant after correction for multiple comparisons; smallest P-value=0.065 for MAP2K5 and common cIMT. The best-performing logic regression tree combined two SNPs in MAP2K5-rs745212 and rs12905175- and common cIMT; this association was not significant, corrected P-value=0.062. CONCLUSION: There was not strong evidence of association between genetic variants in a hemodynamics-responsive gene pathway and atherosclerosis among older adults.

Blood pressure variability and the risk of all-cause mortality, incident myocardial infarction, and incident stroke in the cardiovascular health study. - Suchy-Dicey, Astrid M; Wallace, Erin R; Mitchell, S V Elkind; Aguilar, Maria; Gottesman, Rebecca F; Rice, Kenneth; Kronmal, Richard; Psaty, Bruce M; Longstreth, W T (Am J Hypertens, 2013)
BACKGROUND: Recent reports have linked variability in visit-to-visit systolic blood pressure (SBP) to risk of mortality and stroke, independent of the effect of mean SBP level. This study aimed to evaluate whether variability in SBP is associated with all-cause mortality, incident myocardial infarction (MI), and incident stroke, independent of mean SBP or trends in SBP levels over time. METHODS: The Cardiovascular Health Study is a longitudinal cohort study of vascular risk factors and disease in the elderly. Participants who attended their first 5 annual clinic visits and experienced no event before the 5th visit were eligible (n = 3,852). Primary analyses were restricted to participants not using antihypertensive medications throughout the first 5 clinic visits (n = 1,642). Intraindividual SBP variables were defined using each participant's 5-visit blood pressure measures. Cox proportional hazards models estimated adjusted hazard ratios (HRs) per SD increase in intraindividual SBP variability, adjusted for intraindividual SBP mean and change over time. RESULTS: Over a mean follow-up of 9.9 years, there were 844 deaths, 203 MIs, and 195 strokes. Intraindividual SBP variability was significantly associated with increased risk of mortality (HR = 1.13; 95% confidence interval (CI) = 1.05-1.21) and of incident MI (HR = 1.20; 95%CI = 1.06-1.36), independent of the effect from adjustment factors. Intraindividual SBP variability was not associated with risk of stroke (HR = 1.03; 95% CI = 0.89-1.21). CONCLUSIONS: Long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and MI but not stroke. More research is needed to determine the relationship of BP variability with cardiovascular risk and the clinical implications.
Keywords: Aged; Blood Pressure; Cohort Studies; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Myocardial Infarction; Risk; Stroke; United States